2019
DOI: 10.12681/homvir.20289
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain, consensus, and cryptography in electronic voting

Abstract: Motivated by the recent trends to conduct electronic elections using blockchain technologies, we review the vast literature on cryptographic voting and assess the status of the field. We analyze the security requirements for voting systems and describe the major ideas behind the most influential cryptographic protocols for electronic voting. We focus on the great importance of consensus in the elimination of trusted third parties. Finally, we examine whether recent blockchain innovations can satisfy the strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…e analysts identified weaknesses [63] that could allow an attacker to change or place votes and produce a result that would not match with the actual voters. ese results showed that the system needs to be reverified [60,64]. Ethical hackers even organize a contest at the DefCon conference about how fast voting machines used in America can be hacked, rather than whether they can be hacked [65].…”
Section: Literature On E-voting and Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…e analysts identified weaknesses [63] that could allow an attacker to change or place votes and produce a result that would not match with the actual voters. ese results showed that the system needs to be reverified [60,64]. Ethical hackers even organize a contest at the DefCon conference about how fast voting machines used in America can be hacked, rather than whether they can be hacked [65].…”
Section: Literature On E-voting and Threatsmentioning
confidence: 99%
“…e process essentially consists of hashing a message along with the signer's private key. e recipient of the message can then check whether the signature is valid using the public key provided by the signer [64].…”
Section: Digital Signaturesmentioning
confidence: 99%
“…The lack of centralized controller potentially makes the blockchain more resilient to network failures and attacks. Blockchain is a popular architecture for a number of applications such as cryptocurrency [17,22], massive Internet-of-Things storage [2] and electronic voting [9].…”
Section: Introductionmentioning
confidence: 99%